On the edge - Pitman, Jenny (London: Macmillan, 2002)
Jan Hardy is left to look after her two young children, and to face her bitter mother-in-law alone. But she cannot continue to make a success of the crumbling Welsh farm and the life that goes with it. The only thing she knows about is handling horses. Jan is forced to move to Gloucestershire to be near her parents, increase her profile and raise her stakes as a horse racer, choosing also to look after problem horses and pursue her dream of gaining a training license. This, she hopes, will truly secure a future for her children. As she begins to make her tentative mark on the predominantly male training scene, Jan encounters numerous setbacks from her family and considerable financial difficulties. And to make things worse, certain characters seem determined to make her life as difficult as possible ..." A remarkably accomplished first novel from a woman who knows what she is writing about" - " Daily Express"
Keywords: Horse racing -- Fiction. -- England